STABILITAS ANTIOKSIDAN LOTION EKSTRAK ETANOL DAUN BUAS-BUAS (Premna serratifolia L.) - Puspita, Weni; Puspasari, Heny; Kartika Sari, Dian (Jurnal Insan Farmasi Indonesia, 2025)
This study aims to determine the physical stability and sunscreen activity of lotion ethanol extract of buas-buas leaf. The ethanol extract of buas-buas leaves was obtained by maceration using 70% ethanol solvent. EEDB was then formulated into a lotion with an EEDB concentration (FI: 1%, FII: 2%, FIII : 3%). The EEDB lotion formula was tested for physical stability by cycling test method using a climatic chamber at 40°C ± 2°C and 4 °C ± 2°C for 6 cycles. Tests include organoleptic, homogeneity, viscosity, pH, spreadability, and lotion type. An antioxidant test wa carried out using the DPPH method. The results of the physical stability test on the three EEDB lotion formulas (FI: 1%, FII: 2%, FIII : 3%) showed good physical stability because there were no significant differences during six cycles of storage (p>0.05) with the results of the preparations smelling typical of oleum citri, green-brown in colour, has a semi-solid, homogeneous texture, lotion type M/A, meets the requirements of pH, viscosity and spreadability with the highest average percent inhibition before and after the cycling test, namely in formula III, was 69,89 ± 0,74%.